SOCIO-POLITICAL NEWSPAPER OF THE SOUTHERN REGION (Conferencea, 2023)
The importance of the press, Surkhan oasis newspapers, history of Surkhan Tongi newspaper, information about editors and journalists, topics covered in the newspaper and their content.